Educational Videos on Local Wisdom “Topeng Dance and Basa Walikan” to Motivate the New Culture Clean and Healthy Living Behavior - Apryanto, Frengki; Zunaedi, Rosly; Ramadhani, Rahmaniah (STIKes Patria Husada Blitar, 2025)
Environmental and behavioral factors influence health, so community empowerment is very important to achieve a healthy paradigm. The lack of clean and healthy living behavior in minimizing the risk of disease is due to lack of socialization, availability of facilities, and strong local culture. Further efforts are needed to achieve optimal results. The research aimed to determine the effectiveness of educational video local wisdom